Development of Molybdenum Phosphide Catalysts for Higher Alcohol Synthesis from Syngas by Exploiting Support and Promoter Effects. Issue 5 (12th April 2019) - ten Have, Iris C.; Valle, Eduardo; Gallo, Alessandro; Snider, Jonathan L.; Duyar, Melis S.; Jaramillo, Thomas F.
Abstract : Molybdenum phosphide (MoP) catalysts have recently attracted attention due to their robust methanol synthesis activity from CO/CO2 . Synthesis strategies are used to steer MoP selectivity toward higher alcohols by investigating the promotion effects of alkali (K) and CO‐dissociating (Co, Ni) and non‐CO‐dissociating (Pd) metals. A systematic study with transmission electron microscopy, X‐ray diffraction, X‐ray photoelectron spectroscopy, and X‐ray absorption spectroscopy (XAS) showed that critical parameters governing the activity of MoP catalysts are P/Mo ratio and K loading, both facilitating MoP formation. The kinetic studies of mesoporous silica‐supported MoP catalysts show a twofold role of K, which also acts as an electronic promoter by increasing the total alcohol selectivity and chain length. Palladium (Pd) increases CO conversion, but decreases alcohol chain length. The use of mesoporous carbon (MC) support has the most significant effect on catalyst performance and yields a KMoP/MC catalyst that ranks among the state‐of‐the‐art in terms of selectivity to higher alcohols. Abstract : Molybdenum phosphide (MoP) catalysts have recently attracted attention due to their robust methanol synthesis activity from carbon monoxide (CO) and carbon dioxide (CO2 ). Synthesis strategies are used to steer MoP selectivity during syngas conversion toward higher alcohols; P/Mo ratio, support effects, and the addition of alkali (K), CO‐dissociating (Co, Ni), and non‐CO‐dissociating (Pd) metals are found to have significant effects on catalyst activity.